2018
DOI: 10.1371/journal.pbio.2005380
|View full text |Cite
|
Sign up to set email alerts
|

The actin remodeling protein cofilin is crucial for thymic αβ but not γδ T-cell development

Abstract: Cofilin is an essential actin remodeling protein promoting depolymerization and severing of actin filaments. To address the relevance of cofilin for the development and function of T cells in vivo, we generated knock-in mice in which T-cell–specific nonfunctional (nf) cofilin was expressed instead of wild-type (WT) cofilin. Nf cofilin mice lacked peripheral αβ T cells and showed a severe thymus atrophy. This was caused by an early developmental arrest of thymocytes at the double negative (DN) stage. Importantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 60 publications
(54 reference statements)
1
6
0
Order By: Relevance
“…Several mutations in genes with a role in actin cytoskeleton remodeling of immune cells have been demonstrated to be involved in the pathogenesis of hematological/autoinflammatory diseases, underlining the importance of the actin cytoskeleton in modulating inflammatory responses. Indeed, mutations in the actin-binding protein cofilin (CFL1; Seeland et al, 2018), WAS (Li et al, 2017), DOCK8 (Dasouki et al, 2011), and ARPC1B (Brigida et al, 2018), as well as in RAC2, a Rho GTPase structurally and functionally related to CDC42 (Caye et al, 2015;Hsu et al, 2019), cause abnormal migration, proliferation, and/or differentiation of lymphoid and/or myeloid cells and are associated with features of autoinflammation. Moreover, aberrant actin depolymerization due to an inactivating mutation of the actin-depolymerizing cofactor Wdr1 has been demonstrated to cause in mice an autoinflammatory disease characterized by spontaneous autoinflammation, thrombocytopenia, and neutrophilia (Kim et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Several mutations in genes with a role in actin cytoskeleton remodeling of immune cells have been demonstrated to be involved in the pathogenesis of hematological/autoinflammatory diseases, underlining the importance of the actin cytoskeleton in modulating inflammatory responses. Indeed, mutations in the actin-binding protein cofilin (CFL1; Seeland et al, 2018), WAS (Li et al, 2017), DOCK8 (Dasouki et al, 2011), and ARPC1B (Brigida et al, 2018), as well as in RAC2, a Rho GTPase structurally and functionally related to CDC42 (Caye et al, 2015;Hsu et al, 2019), cause abnormal migration, proliferation, and/or differentiation of lymphoid and/or myeloid cells and are associated with features of autoinflammation. Moreover, aberrant actin depolymerization due to an inactivating mutation of the actin-depolymerizing cofactor Wdr1 has been demonstrated to cause in mice an autoinflammatory disease characterized by spontaneous autoinflammation, thrombocytopenia, and neutrophilia (Kim et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, T-cell maturation within the thymus appears to be maintained. Several mutations affecting actin remodeling have been implicated in T-cell lymphopenia, including cofilin (Cfl1), 40 coronin 1a (CORO1A), 41 Dock8, 42 WASp (WAS), 43 and ARPC1B, 44 each affecting thymocyte development differently. Nonfunctional cofilin leads to a developmental arrest during DN2 to DN3 stage of thymocyte maturation resulting from failure of TCRb surface expression.…”
Section: Effects Of Rac2 Mutations On Lymphocyte Developmentmentioning
confidence: 99%
“…Nonfunctional cofilin leads to a developmental arrest during DN2 to DN3 stage of thymocyte maturation resulting from failure of TCRb surface expression. 40 Different mutations within Coro1a cause lymphopenia by different mechanisms; T cells from Ptcd mice have impaired thymic egress, whereas Koy mice, with unstable Coro1a protein, have reduced thymocyte survival. 40 Dock8 cpm/cpm mice have thymic accumulation of CD4 1 cells and decreased survival of both CD4 1 and CD8 1 cells.…”
Section: Effects Of Rac2 Mutations On Lymphocyte Developmentmentioning
confidence: 99%
“…Studies have shown dephosphorylation of cofilin1 after T cell stimulation (Samstag et al, 1992), however whether phosphorylation is relevant in thymocytes during the initial F-actin burst has not been addressed yet. In a recent study it was shown that expression of a GFP-cofilin1 variant in DN cells that cannot be phosphorylated is blocking T cell development at the DN stage (Seeland et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Cofilin1 has been studied with respect to T cell activation, however its function in the classical differentiation of / T cells in the thymus has been addressed only recently. It was shown that expression of a mutated cofilin1 protein can block T cell differentiation already at the DN stage (Seeland et al, 2018).…”
Section: Introductionmentioning
confidence: 99%